Role of sperm DNA fragmentation in male factor infertility: A systematic review - Chak-Lam Cho (Taylor & Francis Group, 2018)
Objective: To summarise the latest evidence on the role of sperm DNA fragmentation (SDF) in male factor infertility, as SDF has been emerging as a valuable tool for male infertility evaluation. Methods: A search of PubMed was conducted using the keywords ‘sperm DNA fragmentation’ and ‘male infertility’. Studies in languages other than English were excluded. All identified studies were screened and clinical studies in humans were included. Results: In all, 150 articles were included for analysis. Current evidence supports the association between high SDF and poor reproductive outcomes for natural conception and intrauterine insemination. Although the relationship between high SDF and in vitro fertilisation and intracytoplasmic sperm injection is less clear, the negative implication of high SDF on pregnancy loss is evident. Various treatment strategies have been attempted with varying success. The predictive value of SDF testing on outcomes of natural pregnancy and assisted reproduction illustrates its value in clinical practice. Conclusion: The significant role of SDF in male factor infertility is supported by current evidence. The beneficial role of SDF testing in selection of varicocelectomy candidates, evaluation of patients with unexplained infertility and recurrent pregnancy loss, selection of the most appropriate assisted reproductive technique with highest success rate for infertile couples, and assessment of infertile men with modifiable lifestyle factors or gonadotoxin exposure has been recently proposed. Keywords: Sperm DNA fragmentation (SDF), Male infertility, Assisted reproductive technology (ART)